Induction of Trained Immunity by Recombinant Vaccines - Covián, Camila; Ríos, Mariana; Berríos-Rojas, Roslye V.; Bueno, Susan M.; Kalergis, Alexis M. (Frontiers in Immunology, 2021)
Vaccines represent an important strategy to protect humans against a wide variety of pathogens and have even led to the eradication of some diseases. Although every vaccine is developed to induce protective immunity specific for a particular pathogen, some vaccine formulations can also promote trained immunity, which is a non-specific type of memory developed by the innate immune system. It is thought that trained immunity can protect against a wide variety of pathogens, other than those contained in the vaccine formulation. Due that the non-specific memory of the trained immunity-based vaccines (TIbV) seems to be beneficial for the immunized individual, TIbV may represent a potent strategy to contribute to controlling pathogen outbreaks, reducing morbidity and mortality. A wide variety of respiratory viruses, including respiratory syncytial virus (hRSV) and metapneumovirus (hMPV) cause serious illness in children under 5 years old and the elderly. To address this public health problem, we have developed recombinant BCG vaccines that have shown to be safe and immunogenic against hRSV and hMPV. In addition to inducing an adaptive immunity that is specific for the viral antigens, these vaccines could generate trained immunity against other respiratory pathogens. Here, we review some of the features of trained immunity induced by BCG, and we discuss the capability of recombinant BCGs expressing hRSV and hMPV antigens to simultaneously induce specific adaptive immunity as well as non-specific trained immunity. These recombinant BCG vaccines could be considered as TIbV capable of inducing simultaneously the development of specific protection against hRSV and hMPV, as well as non-specific trained-immunity-based protection against other pathogenic viruses.